2015
DOI: 10.1002/jso.23946
|View full text |Cite
|
Sign up to set email alerts
|

A ratiometric threshold for determining presence of cancer during fluorescence-guided surgery

Abstract: Background&Objective Fluorescence-guided imaging to assist in identification of malignant margins has the potential to dramatically improve oncologic surgery. However a standardized method for quantitative assessment of disease-specific fluorescence has not been investigated. Introduced here is a ratiometric threshold derived from mean fluorescent tissue intensity that can be used to semi-quantitatively delineate tumor from normal tissue. Methods Open-field and a closed-field imaging devices were used to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Here we show that development of tumor-specific fluorescence imaging has further ameliorated current deficits in oncologic surgery by extending tumor detection as it disseminates into regional lymph nodes. Interim results from a recent clinical trial (#NCT01987375) demonstrated that cetuximab-IRDye800CW could be safely administered as a tumor-specific contrast agent for use during surgical navigation to aid in the identification of subclinical disease with high sensitivity and specificity(21). It was determined that high levels of fluorescence, as measured by tumor-to-background ratio (TBR), correlated with primary HNSCC and may further represent a tumor-specific method for accurate detection of sentinel lymph node disease.…”
Section: Introductionmentioning
confidence: 99%
“…Here we show that development of tumor-specific fluorescence imaging has further ameliorated current deficits in oncologic surgery by extending tumor detection as it disseminates into regional lymph nodes. Interim results from a recent clinical trial (#NCT01987375) demonstrated that cetuximab-IRDye800CW could be safely administered as a tumor-specific contrast agent for use during surgical navigation to aid in the identification of subclinical disease with high sensitivity and specificity(21). It was determined that high levels of fluorescence, as measured by tumor-to-background ratio (TBR), correlated with primary HNSCC and may further represent a tumor-specific method for accurate detection of sentinel lymph node disease.…”
Section: Introductionmentioning
confidence: 99%
“…The default method for identifying residual tumor using intraoperative imagers has been physician identification from an image. Efforts to define a common quantification metric for imaging tools have centered around the signal-to-background ratio (SBR) 8,9 . Implicit in this metric is a tumor signal significantly above background -true for larger tumor foci, but not necessarily for microscopic disease, which is often just above background contributed by non-specific binding, autofluorescence, and other optical and electronic sources.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, histological processing can take time [9], which is labor intensive and prolongs surgery time. Fluorescence imaging guided cancer resection has been shown to improve the number of complete resections [10-16]. However, fluorescence-based approaches require the injection of a fluorescence imaging agent during surgery and the agent needs to be approved by the U.S. Food and Drug Administration.…”
Section: Introductionmentioning
confidence: 99%